EFFECT OF GMAW TWIN WIRE TANDEM PARAMETERS ON MECHANICAL PROPERTIES OF WELDED JOINTS - Sawrav, Kumar; Bandyopadhyay, Partha Pratim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Tandem welding has the advantage of higher productivity over a limitation considering narrow groove joints. Tandem has higher deposition and heat input. To study the effect of variation in robotic tandem parameters on fatigue properties of welded joints, the following parameters were investigated, viz. first case root & the second pass using a single wire, subsequent run tandem twin and second case using root pass using a single wire, subsequent run using tandem twin wire welding. Butt joint samples were subjected to ultrasonic testing, mechanical & metallurgical testing, and fatigue testing. Found Group 1 tensile strength, yield strength, % elongation & impact value to be 12 %, 9 %, 23 % & 14 %, respectively, higher than Group 2. Explained variations in microhardness & better fatigue life were observed for Group 1. This investigation will help manufacturers in decision-making while selecting tandem parameters considering productivity or reliability.